ANALYSIS OF PARALLEL COUPLING OF CHLOR-ALKALI AND ALKALINE WATER ELECTROLYSIS PROCESS WITH COMBINE CATHODE FLUID CIRCULATION - Pratama, Andri; Sipahutar, Riman; Bizzy, Irwin (AUSTENIT, 2023)
Hydrogen is almost ideal fuel in reducing emissions without CO, CO2, SOX or NOX. Hydrogen can be used through the combustion or Fuel Cell processes so that emissions are low. One of the hydrogen production processes is through electrolysis, both Chlor-Alkali (CA) and Alkaline Water Electrolysis (AWE). Both processes contained a NaOH solution in the CA and catalyst results in AWE. In this test, a combination of CA and AWE processes will be carried out in the fluid circulation at the cathode of two processes. From this study it was found that there was an increase of 11 percent by weight of gas when CA and AWE cathode fluid were circulated in parallel compared to the CA and AWE processes respectively.